2019
DOI: 10.14744/anatoljcardiol.2019.85249
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bariatric surgery on flow mediated dilation and carotid intima-media thickness in patients with morbid obesity: 1-year follow-up study

Abstract: Objective: Obesity is associated with increased cardiovascular (CV) mortality and morbidity. Bariatric surgery (BS) is currently an established therapeutic approach for severely obese patients. Carotid intima-media thickness (CIMT) and brachial artery flow-mediated dilation (FMD) provide important prognostic information beyond traditional CV risk factors. This study aimed to examine the effect of bariatric surgery-induced weight loss on CIMT and brachial artery FMD in morbidly obese patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Surprisingly, there is no conclusive evidence that non-surgical weight loss in patients with obesity is associated with a lower risk of cardiovascular events [ 56 ]. These findings suggest that endothelial function may be improved via weight-independent processes such as endocrine and incretin-mediated effects as well as the improved inflammatory status [ 47 , 57 ]. It is suggested that positive metabolic and cardiovascular effects of bariatric surgery may also be due to changes in intestinal physiology rather than to weight loss alone.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, there is no conclusive evidence that non-surgical weight loss in patients with obesity is associated with a lower risk of cardiovascular events [ 56 ]. These findings suggest that endothelial function may be improved via weight-independent processes such as endocrine and incretin-mediated effects as well as the improved inflammatory status [ 47 , 57 ]. It is suggested that positive metabolic and cardiovascular effects of bariatric surgery may also be due to changes in intestinal physiology rather than to weight loss alone.…”
Section: Discussionmentioning
confidence: 99%
“…We would like to thank the authors of the letter for their criticism about the present study published in the March issue of Anatol J Cardiol 2020; 23: 218-22 (1). The present study revealed that CIMT reduction was not significant from baseline to the 6 th month, whereas it became significant at the 9 th month of followup (1).…”
Section: Author`s Replymentioning
confidence: 46%
“…We found the paper by Elitok et al (1) very interesting. In the study, the authors have investigated the effect of bariatric surgery on carotid intima-media thickness (CIMT).…”
Section: Prognostic Value Of Carotid Intima-media Thicknessmentioning
confidence: 73%
“…However, analysis of these four risk factors also implies that we can improve the function of endotheliocytes through early intervention such as weight loss, a healthy diet and exercise. In some obese people with low FMD, physical exercise or bariatric surgery can increase FMD while losing weight, which suggests the recovery of endothelial injury ( 14 , 47 , 48 ). Aging of endotheliocyte is also not static.…”
Section: Discussionmentioning
confidence: 99%